Socioeconomic Status and its Association with Economic Motivation among the Dairy Entrepreneurs of Kerala - Shyam Suraj S R (Journal of Extension Education, 2023)
The study analyzed the socioeconomic variables of the dairy entrepreneurs of Kerala (India) and their relationship with economic motivation; speciﬁcally, in the three physiographical regions of highland, midland and lowland. Data were collected through survey using structured interview. The results revealed that maximum number of dairy entrepreneurs were male and belonged to elderly group. They were educated mostly up to secondary level and had dairying experience of fewer than 13 years. Largely herd size was between 12-22 animals; and possession of farm assets was weaker than household assets. Majority of the entrepreneurs had gross annual income of below ₹25 lakh from sale of milk and milk products; and local/private sales were more beneﬁcial than co-operative sales. The results showed variance in the socioeconomic variables among the three divisions and hence demands exclusive entrepreneurship development strategies. Regression analysis showed that while milk production and household assets were positively related; experience and sales to dairy cooperatives were negatively related to the economic motivation of the dairy entrepreneurs.